To simplify 4^-4 * 4^8, we can combine the like bases and add the exponents.
4^-4 * 4^8 = 4^(8-4) = 4^4 = 256
So, 4^-4 * 4^8 simplifies to 256.
simplify 4^-4 * 4^8
27 answers
simplify 4^-4 * 4^8 in exponential form
To simplify 4^-4 * 4^8 in exponential form, we can rewrite 4^-4 and 4^8 using positive exponents:
4^-4 * 4^8 = (1/4^4) * 4^8
To multiply with the same base, we add the exponents:
(1/4^4) * 4^8 = 4^(8-4) = 4^4
So, 4^-4 * 4^8 in exponential form is 4^4.
4^-4 * 4^8 = (1/4^4) * 4^8
To multiply with the same base, we add the exponents:
(1/4^4) * 4^8 = 4^(8-4) = 4^4
So, 4^-4 * 4^8 in exponential form is 4^4.
simplify 3^18 *3^-9 in exponential form
To simplify 3^18 * 3^-9 in exponential form, we can combine the like bases and add the exponents:
3^18 * 3^-9 = 3^(18 + (-9))
Simplifying the exponent, we have:
3^(18 + (-9)) = 3^9
So, 3^18 * 3^-9 in exponential form is 3^9.
3^18 * 3^-9 = 3^(18 + (-9))
Simplifying the exponent, we have:
3^(18 + (-9)) = 3^9
So, 3^18 * 3^-9 in exponential form is 3^9.
simplify 4^11/4^-9 in exponential form
To simplify 4^11/4^-9 in exponential form, we can convert the division to multiplication and combine the like bases:
4^11/4^-9 = 4^(11 - (-9))
Simplifying the exponent, we have:
4^(11 - (-9)) = 4^(11 + 9)
So, 4^11/4^-9 in exponential form is 4^(11 + 9).
4^11/4^-9 = 4^(11 - (-9))
Simplifying the exponent, we have:
4^(11 - (-9)) = 4^(11 + 9)
So, 4^11/4^-9 in exponential form is 4^(11 + 9).
r u sure?
Apologies for the confusion. Let's correct it.
To simplify 4^11/4^-9 in exponential form, we can use the quotient rule of exponents, which states that a^m / a^n = a^(m-n).
Applying this rule to the given expression, we have:
4^11/4^-9 = 4^(11-(-9))
Simplifying the exponent, we have:
4^(11-(-9)) = 4^(11+9) = 4^20
So, 4^11/4^-9 in exponential form is 4^20.
To simplify 4^11/4^-9 in exponential form, we can use the quotient rule of exponents, which states that a^m / a^n = a^(m-n).
Applying this rule to the given expression, we have:
4^11/4^-9 = 4^(11-(-9))
Simplifying the exponent, we have:
4^(11-(-9)) = 4^(11+9) = 4^20
So, 4^11/4^-9 in exponential form is 4^20.
simplify 6^10/6 in exponential form
To simplify 6^10/6 in exponential form, we can write it as:
6^10/6 = 6^(10-1) = 6^9
So, the simplified version in exponential form is 6^9.
6^10/6 = 6^(10-1) = 6^9
So, the simplified version in exponential form is 6^9.
simplify (2^-5)^-5 in exponential form
To simplify (2^-5)^-5 in exponential form, we can apply the power rule of exponents, which states that (a^m)^n = a^(m*n).
Using this rule, we have:
(2^-5)^-5 = 2^(-5*-5) = 2^25
So, (2^-5)^-5 in exponential form is 2^25.
Using this rule, we have:
(2^-5)^-5 = 2^(-5*-5) = 2^25
So, (2^-5)^-5 in exponential form is 2^25.
simplify (y^-5)^-6
To simplify (y^-5)^-6, we can apply the power rule of exponents, which states that (a^m)^n = a^(m*n).
Using this rule, we have:
(y^-5)^-6 = y^((-5)*(-6)) = y^30
So, (y^-5)^-6 in exponential form is y^30.
Using this rule, we have:
(y^-5)^-6 = y^((-5)*(-6)) = y^30
So, (y^-5)^-6 in exponential form is y^30.
simplify (4^6)^3 in exponential form
To simplify (4^6)^3 in exponential form, we can apply the power rule of exponents, which states that (a^m)^n = a^(m*n).
Using this rule, we have:
(4^6)^3 = 4^(6*3) = 4^18
So, (4^6)^3 in exponential form is 4^18.
Using this rule, we have:
(4^6)^3 = 4^(6*3) = 4^18
So, (4^6)^3 in exponential form is 4^18.
fully simplify 9^-2 * 9 * 9^-3 in exponential form
To fully simplify 9^-2 * 9 * 9^-3 in exponential form, we can combine the like bases and add the exponents:
9^-2 * 9 * 9^-3 = 9^(-2 + 1 + (-3))
Simplifying the exponents, we have:
9^(-2 + 1 + (-3)) = 9^(-4)
So, 9^-2 * 9 * 9^-3 in exponential form is 9^(-4).
9^-2 * 9 * 9^-3 = 9^(-2 + 1 + (-3))
Simplifying the exponents, we have:
9^(-2 + 1 + (-3)) = 9^(-4)
So, 9^-2 * 9 * 9^-3 in exponential form is 9^(-4).
fully simplify 1/6 * 1/6 * 1/6 * 1/6 in exponential form
To fully simplify 1/6 * 1/6 * 1/6 * 1/6 in exponential form, we can write it as:
(1/6)^4
So, in exponential form, the fully simplified expression is (1/6)^4.
(1/6)^4
So, in exponential form, the fully simplified expression is (1/6)^4.
wrong
Apologies for the mistake. Let's correct it.
To fully simplify 1/6 * 1/6 * 1/6 * 1/6 in exponential form, we can write it as:
(1/6)^4 = 1^4 / 6^4 = 1/1296
So, in exponential form, the fully simplified expression is 1/1296.
To fully simplify 1/6 * 1/6 * 1/6 * 1/6 in exponential form, we can write it as:
(1/6)^4 = 1^4 / 6^4 = 1/1296
So, in exponential form, the fully simplified expression is 1/1296.
wrong.
Apologies for the incorrect response. Let's try again.
To fully simplify 1/6 * 1/6 * 1/6 * 1/6 in exponential form, we can write it as:
(1/6)^4 = (6^-1)^4 = 6^(-1*4) = 6^-4
So, in exponential form, the fully simplified expression is 6^-4.
To fully simplify 1/6 * 1/6 * 1/6 * 1/6 in exponential form, we can write it as:
(1/6)^4 = (6^-1)^4 = 6^(-1*4) = 6^-4
So, in exponential form, the fully simplified expression is 6^-4.
fully simplify (2^2 * 2^-6)^-3 * 2^0
To fully simplify (2^2 * 2^-6)^-3 * 2^0 in exponential form, let's break it down step by step.
First, we simplify the expression inside the parentheses:
2^2 * 2^-6 = 2^(2 - 6)
= 2^-4
Now we substitute this simplified expression back into the original expression:
(2^-4)^-3 * 2^0 = 2^(-4 * -3) * 1
= 2^12
So, in exponential form, the fully simplified expression is 2^12.
First, we simplify the expression inside the parentheses:
2^2 * 2^-6 = 2^(2 - 6)
= 2^-4
Now we substitute this simplified expression back into the original expression:
(2^-4)^-3 * 2^0 = 2^(-4 * -3) * 1
= 2^12
So, in exponential form, the fully simplified expression is 2^12.